A class of semiprimitive groups that are graph‐restrictive. (4th September 2014) - Giudici, Michael; Morgan, Luke
Abstract : We prove that an infinite family of semiprimitive groups is graph‐restrictive. This adds to the evidence for the validity of the Potočnik–Spiga–Verret Conjecture and increases the minimal imprimitive degree for which this conjecture is open to 12. Our result can be seen as a generalization of the well‐known theorem of Tutte on cubic graphs. The proof uses the amalgam method, adapted to this new situation.